A Comparative Phytochemical Investigation of the Greek Members of the Genus Helichrysum Mill., with Emphasis on the Local Endemic Helichrysum amorginum Boiss and Orph - Iordanis Samanidis; Nikos Krigas; Vassilis Athanasiadis; Ioannis Makrygiannis; Martha Mantiniotou; Stavros I. Lalas (Plants)
The members of the genus Helichrysum Mill. are notable for producing a diverse range of structurally intricate secondary metabolites, being the focus of current phytochemical research. Their importance is recognized as several species hold significant ethnopharmacological value, being traditionally used to address ailments in human systems, such as respiratory, gastrointestinal, and urinary conditions, among others. This study used liquid chromatography coupled with high-resolution mass spectrometry results to present the phytochemical composition of non-volatile secondary metabolites in 11 Greek Helichrysum taxa (species and subspecies). For the first time, their total polyphenol content is comparatively assessed and an overview of the non-volatile compounds for five Endangered or Critically Endangered Greek Endemic Helichrysum taxa are presented herein. Almost all of the studied Helichrysum taxa differed significantly in the mean values of their polyphenolic content, except for H. doerfleri and H. heldreichii. A particular emphasis was placed on extracting polyphenols from a cultivated genotype of H. amorginum using aqueous pressurized liquid extraction as an alternative to the traditional organic solvent extraction method. Analysis by high-performance liquid chromatography revealed that this method increased the concentration of neochlorogenic acid and astragalin, compared to other extraction conditions. These findings highlight the potential of alternative extraction techniques for obtaining natural products from sustainably managed phytogenetic sources.